A survey in uncharted territory: A collaborative study to explore the approach to atopic dermatitis patient management in allopathy and naturopathy. Issue 1 (19th November 2019) - Dhossche, Julie; Corn, Josh; Simpson, Eric L.; Funk, Tracy
Abstract: Background: Atopic dermatitis (AD) patients frequently use both conventional and complementary medicines for treatment. Allopathic and naturopathic providers may be unaware of each other's approach to AD diagnosis, skin care, and treatment, affecting patient and provider communication, patient safety, and potential for collaborative studies. Objective: To identify core commonalities and differences in allopathic and naturopathic approach to AD. Methods: Thirty allopathic and 21 naturopathic providers completed an 11‐question free‐text comment survey, covering patient education and evaluation, skin care, and treatment of AD. Qualitative content analysis detected key ideas and concepts, and word cloud analysis provided a quantitative visual representation of recurrent words in each group's responses. Results: All respondents indicated using similar physical features to diagnose AD. In both allopathic and naturopathic fields, the majority of providers did not perform routine testing for AD diagnosis. Skin care with moisturization and "soak‐and‐seal" bathing practices were routine in both fields. Naturopathic providers heavily emphasized the role of food and diet in AD pathogenesis, education, and management, while allopathic providers indicated little to no role for food and diet in AD. For treatment, allopathic providers favored topical steroids, phototherapy, and immunomodulators, whereas naturopathic providers recommended botanicals, supplements, and other complementary and alternative methods. Conclusions: Providers should be aware of the differences between allopathic and naturopathic providers and their approach to AD management, particularly concerning the role of food and diet. There may be opportunities to harmonize skin care regimens for patients given similar approach in both fields, and to collaborate further on studies of diet in AD and treatments not yet effectively tested.